PERANAN AKUNTANSI TERHADAP MANAJEMEN KEUANGAN USAHA KECIL MENENGAH (UKM) DAN KOPERASI DI INDONESIA - Riswan Riswan (Faculty of Economics and Business Universitas Jenderal Soedirman, 2016)
This article discusses the importance of accounting for SMEs and cooperatives, accounting Role Of Financial Management of SMEs and cooperatives in Indonesia and Accountability accounting for SMEs and Cooperatives in Indonesia.